2018
DOI: 10.4300/jgme-d-17-00633.1
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Trends in the Orthopedic Surgery Residency Match

Abstract: There is an association among hometown, undergraduate institution, and medical school for the training program location in which orthopedic surgery residents match, with variability in locations matched at state and census division levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…Evidence supporting most of these perceptions exists. Cox et al 13 found a strong association between the location applicants matched for residency and where the applicants previously lived or attended school. In addition, Schrock et al 14 found that a higher proportion of matched applicants come from top 40 NIH-funded schools.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting most of these perceptions exists. Cox et al 13 found a strong association between the location applicants matched for residency and where the applicants previously lived or attended school. In addition, Schrock et al 14 found that a higher proportion of matched applicants come from top 40 NIH-funded schools.…”
Section: Discussionmentioning
confidence: 99%
“… 1 This geographic trend is also present for other surgical subspecialties. 2 , 3 Silvestre reasons that existing professional networks incentivize these regional trends. 1 Professional relationships likely play an influential role in the match process.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, this is the first study to report the program-provided career and personal interests of orthopaedic surgery residents. Our analyses provide a four-year update of orthopaedic surgery resident geographic distribution trends compared with the lone previous study 11 ; however, this study also includes data of both allopathic and osteopathic orthopaedic surgery programs, as well as a more precise determination of mean geographical distance traveled by each resident from university and medical school to residency.…”
Section: Discussionmentioning
confidence: 99%
“…Existing orthopaedic surgery residency programs were identified on the Electronic Residency Application Service (ERAS) website, a methodology adapted from previous studies of similar focus. 8 , 11 Orthopaedic residency program websites were identified through ERAS listings and search engine queries through Google. If an ERAS listing did not include a direct link to a program's website, a Google search was performed by the authors (N.S.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation